Review: Approaches to teaching the history of the English language: Pedagogy in practice. By Mary Hayes & Allison Burkette (eds.). Oxford: Oxford University Press, 2017. Pp. 480. ISBN: 9780190611057. - Walkden, George; Hejná, Michaela (Studia Anglica Posnaniensia, 2018)
Review: Approaches to teaching the history of the English language: Pedagogy in practice. By Mary Hayes & Allison Burkette (eds.). Oxford: Oxford University Press, 2017. Pp. 480. ISBN: 9780190611057. Reviewed by George Walkden (University of Konstanz) and Michaela Hejná (Aarhus University).